2005
DOI: 10.1021/om049080w
|View full text |Cite
|
Sign up to set email alerts
|

Copolymerization of Ethylene with Methyl Methacrylate with Neutral Nickel(II) Complexes Bearing β-Ketoiminato Chelate Ligands

Abstract: New neutral nickel(II) complexes bearing asymmetric β-ketoiminato (N,O) ligands (5ac), [(2,6-i Pr 2 C 6 H 3 )NC(R 2 )C(H)C(R 1 )O]Ni(Ph)(PPh 3 ), have been synthesized. X-ray crystal structures reveal that each of complexes 5a-c adopts a near square-planar coordination geometry and the triphenylphosphine group is always trans to the arylamine group. With modified methylaluminoxane (MMAO) as a cocatalyst, complexes 5a-c can promote the polymerization of methyl methacrylate (MMA) in excellent yields (>98%), pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
52
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 93 publications
(56 citation statements)
references
References 39 publications
4
52
0
Order By: Relevance
“…However, although the most expensive palladium α‐diimine catalysts were able to produce ethylene‐acrylate or propene‐acrylate copolymers under certain experimental conditions, their nickel α‐diimine counterparts were easily poisoned by polar comonomers 5, 6. In contrast, nickel catalysts based on neutral ligands exhibiting a mixed donor atom set (N,O or P,O) are a priori good candidates for copolymerization due to their less electrophilic center 7–11. Thus, by increasing the positive charge density at the metal center, we would expect to see an increase in activity as preserving the capacity of the aforementioned catalysts to incorporate polar comonomers.…”
Section: Introductionmentioning
confidence: 99%
“…However, although the most expensive palladium α‐diimine catalysts were able to produce ethylene‐acrylate or propene‐acrylate copolymers under certain experimental conditions, their nickel α‐diimine counterparts were easily poisoned by polar comonomers 5, 6. In contrast, nickel catalysts based on neutral ligands exhibiting a mixed donor atom set (N,O or P,O) are a priori good candidates for copolymerization due to their less electrophilic center 7–11. Thus, by increasing the positive charge density at the metal center, we would expect to see an increase in activity as preserving the capacity of the aforementioned catalysts to incorporate polar comonomers.…”
Section: Introductionmentioning
confidence: 99%
“…Although early transition metal catalyst currently dominates the industrial process of olefin polymerization, there has been a trend toward the development of the catalysts containing late transition metal elements because of the potential to yield polymers with different microstructures and more tolerant of functionalized monomers 1–32. An important advance in late transition metal catalyst for olefin polymerization was described by Brookhart and coworkers, who showed that Ni(II) and Pd(II) complexes incorporating bulky α‐diimine ligands are capable of polymerizing ethylene to high molecular weight branched polyethylenes 5–9…”
Section: Introductionmentioning
confidence: 99%
“…Similar anilinoenolate Ni complexes also promote copolymerization of ethylene with methyl methacrylate [110][111][112][113]. The complexes having ligand with acyclic structure require B(C 6 F 5 ) 3 for the activation, whereas the complex of the ligand having Chart 4.6 Ni catalysts with salicylaldimine ligands cyclic substituent (6e) acts as a single-component catalyst.…”
Section: Catalyst Having An Imine-aryloxo (Phenoxyimine) Type Ligandsmentioning
confidence: 99%